2006
DOI: 10.1177/0363546506294469
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Local Administration of Vascular Endothelial Growth Factor on Mechanical Characteristics of the Semitendinosus Tendon Graft after Anterior Cruciate Ligament Reconstruction in Sheep

Abstract: Exogenous VEGF application for ACL reconstruction can induce an increase in knee laxity and a decrease in the stiffness of the grafted tendon at least temporarily after ACL reconstruction. These potentially negative mechanical effects need to be taken into account when considering clinical use of VEGF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
152
3
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(165 citation statements)
references
References 23 publications
8
152
3
2
Order By: Relevance
“…11,41 In the present study, biomechanical testing showed significant improvements in the functional healing of the ligaments in the MDSC-VEGF and the MDSC groups; however, there was no significant difference observed between these 2 groups. Some studies have reported that VEGF was produced at its highest levels only after the inflammatory phase in the natural healing process of the injured ligament and tendon and that VEGF and blood vessel formation crested between 5 and 9 days post-injury.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…11,41 In the present study, biomechanical testing showed significant improvements in the functional healing of the ligaments in the MDSC-VEGF and the MDSC groups; however, there was no significant difference observed between these 2 groups. Some studies have reported that VEGF was produced at its highest levels only after the inflammatory phase in the natural healing process of the injured ligament and tendon and that VEGF and blood vessel formation crested between 5 and 9 days post-injury.…”
Section: Discussioncontrasting
confidence: 53%
“…[9][10][11] Among the variety of growth factors regulating angiogenesis, 12 the most potent known is the vascular endothelial growth factor (VEGF). 13 Recent studies have shown that VEGF plays an important role in tissue healing through angiogenesis induction.…”
mentioning
confidence: 99%
“…Kobayashi et al 26 indicated that enhanced neovascularization and formation of granulation tissue induced the healing of a partially injured ACL with growth factor. A sheep study by Yoshikawa et al 27 using a VEGF solution demonstrated that newly formed vessels and infiltrative fibroblasts were more abundant in tendons that had been soaked in VEGF solution prior to being grafted into a ruptured ACL than in tendons that had been soaked in PBS. Unfortunately, growth factor is very expensive.…”
Section: Angiogenesis After Implantation In Vivomentioning
confidence: 99%
“…Therefore, we conducted a following large animal model study to clarify if recombinant VEGF application affects the mechanical properties of the grafted tendon after ACL reconstruction before its clinical application of recombinant VEGF therapy to ACL reconstruction. In this experiment, we used mature female Suffolk sheep (Yoshikawa, 2006b) . We harvested the semitendinosus tendon from the right leg and then soaked the tendon in recombinant human VEGF with 10-ml phosphate buffered saline (PBS) for 15 minutes and then perfrmed ACL reconstruction using this semitendinosus tendon in the same leg (Fig.…”
Section: Growth Factor Application For Enhancement Of Angiogenesismentioning
confidence: 99%
“…Ju (2006)). Yoshikawa (2006b)). Group I: the femur-graft-tibia complex 12 weeks after ACL reconstruction with semitendinosus tendon graft soaked in phosphate buffered saline, Group II: the femur-graft-tibia complex 12 weeks after ACL reconstruction with semitendinosus tendon graft soaked in VEGF solution, Normal: normal the femur-graft-tibia complex with no treatment.…”
Section: Growth Factor Application For Enhancement Of Angiogenesismentioning
confidence: 99%